A vision on the future of articular cartilage repair - M Cucchiarini; H Madry; F Guilak; DB Saris; MJ Stoddart; M Koon Wong; P Roughley (European Cells & Materials, 2014)
An AO Foundation (Davos, Switzerland) sponsored workshop "Cell Therapy in Cartilage Repair" from the Symposium "Where Science meets Clinics" (September 5-7, 2013, Davos) gathered leaders from medicine, science, industry, and regulatory organisations to debate the vision of cell therapy in articular cartilage repair and the measures that could be taken to narrow the gap between vision and current practice. Cell-based therapy is already in clinical use to enhance the repair of cartilage lesions, with procedures such as microfracture and articular chondrocyte implantation. However, even though long term follow up is good from a clinical perspective and some of the most rigorous randomised controlled trials in the regenerative medicine/orthopaedics field show beneficial effect, none of these options have proved successful in restoring the original articular cartilage structure and functionality in patients so far. With the remarkable recent advances in experimental research in cell biology (new sources for chondrocytes, stem cells), molecular biology (growth factors, genes), biomaterials, biomechanics, and translational science, a combined effort between scientists and clinicians with broad expertise may allow development of an improved cell therapy for cartilage repair. This position paper describes the current state of the art in the field to help define a procedure adapted to the clinical situation for upcoming translation in the patient.